A Comparative Study of Bladder Neck Preservation Versus Bladder Neck Reconstruction during Retropubic Radical Prostatectomy in Term of Urinary incontinence - Hammood , Ayman Hamid; Al-Ebrahimee , Hayder Makki Baqer; Al-Maliki , Shaymaa Jasim Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Background: Urinary continence remains a critical functional outcome following radical prostatectomy. Bladder neck preservation has been advocated to improve postoperative continence. While BNR has been widely reported, evidence focusing on the impact of BNP, particularly on early continence following open retropubic radical prostatectomy (RRP), remains limited. Objective: To evaluate early and late urinary continence outcomes following bladder neck preservation during open retropubic radical prostatectomy and to compare these results with bladder neck reconstruction outcomes reported in the literature. Patients and Methods: This prospective study was conducted at Al-Sadr Teaching Hospital, Al-Najaf, between January 2022 and January 2025. Patients with clinically localized prostate cancer underwent open retropubic radical prostatectomy with intentional bladder neck preservation. Postoperative follow-up was performed at 3, 6, and 12 months. Primary outcomes included early and late urinary continence recovery. Secondary outcomes included vesicourethral anastomotic stenosis and surgical margin status. Results: Bladder neck preservation was associated with favorable early continence recovery, with a notable proportion of patients achieving continence within the first postoperative months. Continence rates further improved over time, resulting in high late continence rates at 12 months, comparable to late continence outcomes reported in bladder neck reconstruction series. At the 3-month follow-up, urinary continence was achieved in 90% of patients. This proportion further increased to 95% at 6 months. By the 12-month follow-up, all patients (100%) had achieved full urinary continence. Vesicourethral anastomotic stenosis occurred in two patients and was successfully managed endoscopically. All patients demonstrated negative surgical margins. Conclusion: Bladder neck preservation during open retropubic radical prostatectomy appears to confer its principal functional advantage in enhancing early urinary continence, while maintaining late continence outcomes comparable to bladder neck reconstruction techniques reported in the literature. This approach offers a meaningful early quality-of-life benefit without compromising oncological safety and represents a viable alternative to bladder neck reconstruction.